2004
DOI: 10.1261/rna.5164904
|View full text |Cite
|
Sign up to set email alerts
|

Preferential translation of cold-shock mRNAs during cold adaptation

Abstract: Upon temperature downshift below the lower threshold of balanced growth (∼20°C), the Escherichia coli translational apparatus undergoes modifications allowing the selective translation of the transcripts of cold shock-induced genes, while bulk protein synthesis is drastically reduced. Here we were able to reproduce this translational bias in E. coli cell-free extracts prepared at various times during cold adaptation which were found to display different capacities to translate different types of mRNAs as a fun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
125
0
3

Year Published

2005
2005
2020
2020

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 98 publications
(136 citation statements)
references
References 23 publications
8
125
0
3
Order By: Relevance
“…In E. coli, cold shock leads to an increase in IF3 abundance relative to ribosome abundance, leading to the preferential translation of cold-shock mRNAs (37). At low temperature, IF3 increases the binding rate of fMet-tRNA to ribosomes associated with cold-shock mRNA, increases the pool size of 30S subunits, and lowers the fidelity of translation of non-cold-shock mRNAs (38).…”
Section: Discussionmentioning
confidence: 99%
“…In E. coli, cold shock leads to an increase in IF3 abundance relative to ribosome abundance, leading to the preferential translation of cold-shock mRNAs (37). At low temperature, IF3 increases the binding rate of fMet-tRNA to ribosomes associated with cold-shock mRNA, increases the pool size of 30S subunits, and lowers the fidelity of translation of non-cold-shock mRNAs (38).…”
Section: Discussionmentioning
confidence: 99%
“…The transcript of cspA (cspAmRNA) was selected as a paradigm cold-shock mRNA since it has been demonstrated that it is preferentially and efficiently transcribed and translated following cold shock (Gualerzi et al 2003). On the other hand, the transcript of cspD (cspDmRNA) was selected as a paradigm non-cold-shock mRNA because it is expressed during stationary phase and following glucose starvation (Yamanaka and Inouye 1997) but is poorly translated at low temperature (Giuliodori et al 2004).…”
Section: De Novo Synthesis Of If3 After Cold Shockmentioning
confidence: 99%
“…However, after cold stress, the level of the IFs increases in the absence of a corresponding increase of the number of ribosomes, thereby creating an exceptional imbalance in the IFs/ribosome ratio. This seems to be at least one of the causes of the above mentioned cold shock translational bias (Giuliodori et al 2004).…”
Section: Introductionmentioning
confidence: 97%
See 2 more Smart Citations